Coaching anticipatory skill in badminton: laboratory versus field-based perceptual training - Hagemann, N.; Memmert, D. (Journal of Human Movement Studies, 2006)
This study compared a video-based program for coaching anticipatory cues in badminton with real field training. 48 College students (21 female) aged 20-28 years completed voluntary badminton courses in one of three equal-sized groups: field-based perceptual training, laboratory-based perceptual training and placebo. Performance was assessed with the Badminton Anticipation Test (BAT 1.0) before and after training and in a retention test two weeks later. Results showed significant improvements in both training groups compared with the placebo group at all measurement times. Differentiated analyses revealed that improvement in the laboratory-based group was basically due to a specific adaptation to the person modeling opponents1 strokes in the video clips. These participants particularly learned to improve their anticipation of the length of the shot (reduction of depth error). The discussion considers the significance of error components (lateral and depth error), the time window of learning effects, and the specificity of the movement demonstration.